How Mergers and Acquisitions Affected the Basic Accounting Elements of Greek Banks During the Euro Years 2002-2018 - Georgios, Kyriazopoulos; Maria-Rafailia, Logotheti (Journal of Accounting, Business and Finance Research, 2019)
During the years 2002-2018 a big wave of mergers and acquisitions took place in Greek Banking System. We have two big time periods that mergers and acquisitions occurred in the Greek Banking System. The first one includes the years 2002-2009 that the main domestic reasons for mergers and acquisitions in the Greek Banking System were the profit and the size so as to be able to expand mainly to the Balkan Countries with cross border mergers and acquisitions for more profit. The second one includes the years 2010-2018 that the world financial crisis affected the Greek Banking System. So the main reason for domestic mergers and acquisitions among the Greek Banks were the strengthening of them against aggressive takeovers, the economies of scale, risk of bankruptcy and recapitalization. In this paper we try to find out how these two time periods of mergers and acquisitions in the Greek Banking System affected the basic accounting elements such as Assets, Loans Equity, all kind of profits, Deposit even the personnel, of the remaining four Systemic Greek Banks. The remaining four Systemic Greek Banks that we examine in this paper are Eurobank, National Bank, Alpha Bank and Bank of Piraeus.